Kesetaraan dan Perbedaan Laki-laki dan Perempuan: Kritik terhadap Gerakan Feminisme - Lina Gunawan (Societas Dei: Jurnal Agama dan Masyarakat, 2016)
ABSTRACT: This article with a title: The Equality and Distinction Between Man and Woman: A Critique to the Feminist Movement", will firstly discuss about the feminist movement comprehensively and afterward itu will discuss about the feminist movement within Christianity, gender-equality issues, as well as the distinction between man and woman from the view of Christian feminism. After these, it will be discussed gender-equality issues and the distinction between man and woman from the perspective of Reformed theology. Then a critique to the feminist movement within Christianity will be discussed. The finding of this article is that the feminist movement within Christianity has indeed grown a better appreciation for the woman, especially in the equality between man and woman wich is a reality. The consequence is the authority of the Bible is accused by this Christian feminist movement. KEYWORDS: feminism, Christian feminism, equality, distinction, Reformed theology.